2018
DOI: 10.1097/dss.0000000000001337
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factor Enhanced Fat Graft Survival: A Comparative Study

Abstract: In this preliminary study, CGF treatment improved the survival and quality of fat grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 20 publications
0
37
0
3
Order By: Relevance
“…Although under treatment with CGF extracts, higher cells proliferation in a dose‐dependent manner was approved by Jin et al, enhanced cell migration, and differentiation in the low doses (<50%) of CGF was noticeable (Jin et al, ). Two studies compared effect of CGF with PRF, and the results show that PRF is more efficient in osteogenic differentiation of stem cells, while CGF is more efficient in vascular differentiation (Hong et al, ; Hu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although under treatment with CGF extracts, higher cells proliferation in a dose‐dependent manner was approved by Jin et al, enhanced cell migration, and differentiation in the low doses (<50%) of CGF was noticeable (Jin et al, ). Two studies compared effect of CGF with PRF, and the results show that PRF is more efficient in osteogenic differentiation of stem cells, while CGF is more efficient in vascular differentiation (Hong et al, ; Hu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, four studies showed that a high dose of CGF does not have a positive effect. In more efficient in vascular differentiation (Hong et al, 2018;Hu et al, 2018).…”
Section: Effect Of Cgf On Stem Cellsmentioning
confidence: 99%
“…PRP'ye göre daha yoğundur ve daha yüksek miktarlarda büyüme faktörü içermektedir ve trombin olmadan aktive olabilmektedir (16,17). Aynı zamanda vasküler dayanıklılık, neovaskülarizasyon ve anjiogenezde rol alan CD34+ kök hücre içermektedir (15,23). CGF'in yumuşak doku iyileşmesinde PRP'ye göre daha etkili olduğu raporlanmıştır (24).…”
Section: Cerrahi Teknikunclassified
“…Klinik ve deneysel çalışmalarda CGF'in kemik, kıkırdak ve periferik sinir doku üzerine proliferatif etkileri ve greftlerin yaşayabilirliği üzerine olumlu etkileri gösterilmiştir (17,18). (17)(18)(19)23,27). Bu çalışmada ise CGF'in flep yaşayabilirliği üzerinde de anlamlı artış sağladığı görüldü.…”
Section: Cerrahi Teknikunclassified
See 1 more Smart Citation